Revisiting Exchange Rate Shocks on Macroeconomic Variables in China using Time-Varying VAR Model - Bahmani-Oskoee, Mohsen; Cai, Yifei; Chang, Tsangyao; Liu, Shanshan (The Economics and Finance Letters, 2022)
In this study we analyze exchange rate shocks in China on its macroeconomic variables by apply TVP-VAR modeling approach. Three-dimensional impulse response functions reveal that GDP, CPI and interest rate are affected in the short run and long run. Our findings have important policy implications for the Chinese government conducting exchange rate policy.